Intergenerational transmission of alloparental behavior and oxytocin and vasopressin receptor distribution in the prairie vole - Perkeybile, Allison M.; Delaney-Busch, Nathanial; Hartman, Sarah; Grimm, Kevin J.; Bales, Karen L. (Frontiers in Behavioral Neuroscience, 2015)
Variation in the early environment has the potential to permanently alter offspring behavior and development. We have previously shown that naturally occurring variation in biparental care of offspring in the prairie vole is related to differences in social behavior of the offspring. It was not, however, clear whether the behavioral differences seen between offspring receiving high compared to low amounts of parental care were the result of different care experiences or were due to shared genetics with their high-contact or low-contact parents. Here we use cross-fostering methods to determine the mode of transmission of alloparental behavior and oxytocin receptor (OTR) and vasopressin V1a receptor (V1aR) binding from parent to offspring. Offspring were cross-fostered or in-fostered on postnatal day 1 and parental care received was quantified in the first week postpartum. At weaning, offspring underwent an alloparental care test and brains were then collected from all parents and offspring to examine OTR and V1aR binding. Results indicate that alloparental behavior of offspring was predicted by the parental behavior of their rearing parents. Receptor binding for both OTR and V1aR tended to be predicted by the genetic mothers for female offspring and by the genetic fathers for male offspring. These findings suggest a different, sex-dependent, role of early experience and genetics in shaping behavior compared to receptor distribution and support the notion of sex-dependent outcomes.